MAVS disruption impairs downstream signaling and results in higher virus replication levels of salmonid alphavirus subtype 3 but not infectious pancreatic necrosis virus in vitro - Xu, Cheng; Gamil, Amr A. A.; Wang, Xiaolin; Munang’andu, Hetron Mweemba; Evensen, Øystein (Frontiers in Immunology, 2024)
The mitochondrial anti-viral signaling (MAVS) protein is an intermediary adaptor protein of retinoic acid-inducible gene-1 (RIG-I) like receptor (RLR) signaling, which activates the transcription factor interferon (IFN) regulatory factor 3 (IRF3) and NF-kB to produce type I IFNs. MAVS expression has been reported in different fish species, but few studies have shown its functional role in anti-viral responses to fish viruses. In this study, we used the transcription activator-like effector nuclease (TALEN) as a gene editing tool to disrupt the function of MAVS in Chinook salmon (Oncorhynchus tshawytscha) embryonic cells (CHSE) to understand its role in induction of interferon I responses to infections with the (+) RNA virus salmonid alphavirus subtype 3 (SAV-3), and the dsRNA virus infectious pancreatic necrosis virus (IPNV) infection. A MAVS-disrupted CHSE clone with a 7-aa polypeptide (GVFVSRV) deletion mutation at the N-terminal of the CARD domain infected with SAV-3 resulted in significantly lower expression of IRF3, IFNa, and ISGs and increased viral titer (1.5 log10) compared to wild-type. In contrast, the IPNV titer in MAVS-disrupted cells was not different from the wild-type. Furthermore, overexpression of salmon MAVS in MAVS-disrupted CHSE cells rescued the impaired type I IFN-mediated anti-viral effect against SAV-3.